2012
DOI: 10.1002/adfm.201201371
|View full text |Cite
|
Sign up to set email alerts
|

Flexible, Multifunctional, Magnetically Actuated Nanocomposite Films

Abstract: Filler nanoparticles greatly enhance the performance of polymers and minimize filler content in the resulting nanocomposites. At the same time, they challenge the manufacturing of such nanocomposites by filler agglomeration and non‐uniform spatial distribution. Here, multifunctional nanocomposite films are made by capitalizing on flame‐synthesis of ceramic or metal filler nanoparticles followed by rapid, in situ deposition on sacrificial substrates, resulting in a filler film with controlled porosity. The poly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
52
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(53 citation statements)
references
References 40 publications
(62 reference statements)
1
52
0
Order By: Relevance
“…Up to now, the contact resistance based pressure sensors [46][47][48][49] have demonstrated good repeatability with fast response time (in seconds timescale). However, neither sensitivity nor accessible pressure region of the present contact resistance based sensors is suffi cient to compete with that of human skin.Mechanical ductility of the sensor materials, such as carbon based materials, [50][51][52] ZnO, [ 53 ] or composite materials, [54][55][56][57] is critical for the performance of a pressure sensor. Moreover, it has also been demonstrated that specifi c structures fabricated in the sensor enhance its performance.…”
mentioning
confidence: 99%
“…Up to now, the contact resistance based pressure sensors [46][47][48][49] have demonstrated good repeatability with fast response time (in seconds timescale). However, neither sensitivity nor accessible pressure region of the present contact resistance based sensors is suffi cient to compete with that of human skin.Mechanical ductility of the sensor materials, such as carbon based materials, [50][51][52] ZnO, [ 53 ] or composite materials, [54][55][56][57] is critical for the performance of a pressure sensor. Moreover, it has also been demonstrated that specifi c structures fabricated in the sensor enhance its performance.…”
mentioning
confidence: 99%
“…plasmonic and phosphorescent-superparamagnetic actuators have been prepared by depositing nanoparticles from the flame into a polymer film (e.g. PMMA) and covering the nanoparticle film with spin coated layer of the same polymer as the substrate, resulting in a nanoparticle layer fully embedded in the polymer (Sotiriou et al, 2013). Also conductive polymer nanocomposites have been fabricated with similar process (Blattmann et al, 2015).…”
Section: Accumulation Of Particle Depositmentioning
confidence: 99%
“…By the addition of the nanofillers, the improvement in mechanical properties not only is limited to stiffness or strength, but it is also extended to improve the time-dependent properties [4]. Alternatively, the enhanced crystallization behaviour under flow conditions and other physical properties of high performance nanocomposites is mainly due to the high aspect ratio and/or the high surface area of the fillers, since nanoparticulates have extremely high surface area to volume ratio when good dispersion is achieved [5][6][7]. Nanoparticle dispersion in the polymer matrix is a key issue, which limits the applicable particle volume fraction and therefore also the multi-functionality of the composite material.…”
Section: Introductionmentioning
confidence: 99%